Genomic landscape of advanced prostate cancer patients with BRCA1 versus BRCA2 mutations as detected by comprehensive genomic profiling of cell-free DNA - Swami, Umang; Zimmerman, Raquel Mae; Nussenzveig, Roberto H.; Hernandez, Edgar Javier; Jo, Yeonjung; Sayegh, Nicolas; Wesolowski, Sergiusz; Kiedrowski, Lesli A.; Barata, Pedro C.; Lemmon, Gordon Howard; Bilen, Mehmet A.; Heath, Elisabeth I.; et al. (Frontiers in Oncology, 2022)
BRCA1-mutated prostate cancer has been shown to be less responsive to poly (ADP-ribose) polymerase (PARP) inhibitors as compared to BRCA2-mutated prostate cancer. The reason for this differential response is not clear. We hypothesized this differential sensitivity to PARP inhibitors may be explained by distinct genomic landscapes of BRCA1 versus BRCA2 co-segregating genes. In a large dataset of 7,707 men with advanced prostate cancer undergoing comprehensive genomic profiling (CGP) of cell free DNA (cfDNA), 614 men harbored BRCA1 and/or BRCA2 alterations. Differences in the genomic landscape of co-segregating genes was investigated by Fisher’s exact test and probabilistic graphical models (PGMs). Results demonstrated that BRCA1 significantly associates with 6 other genes, while BRCA2 was not significantly associated with any gene. These findings suggest BRCA2 may be the main driver mutation, while BRCA1 mutations tend to co-segregate with mutations in other molecular pathways contributing to prostate cancer progression. These hypothesis generating data may explain the differential response to PARP inhibition and guide towards development of combinatorial drug regimens in those with BRCA1 mutation.